Experimental study on mechanical and microstructural properties of cement-based paste for shotcrete use in high-temperature geothermal environment. (20th June 2018) - Cui, Shengai; Liu, Pin; Su, Jiao; Cui, Enqi; Guo, Chen; Zhu, Bing
Highlights: A simulation method for an 85 °C high-temperature geothermal environment was designed. The hydration state was stimulated by the high-temperature geothermal environment. Co-doping of fly ash and silica fume is recommended in this environment. Abstract: In order to study the mechanical and microstructural properties of cement-based paste for shotcrete use in a high-temperature geothermal environment, the distinct environment was simulated in a laboratory where mechanical testing, thermogravimetric and differential thermal analyses, and scanning electron microscopy were conducted. Compared to the curing environment at 20 °C, the hydration state of the cement-based paste for shotcrete use was transformed to a state similar to that of cement-based paste for ordinary concrete within a shorter time, owing to the stimulation of the high-temperature geothermal environment. The cement-fly ash composite paste for shotcrete use cured in the high-temperature environment still exhibited lower strength in the early ages, yet slightly higher strengths at a 28-day age than pure cement-based paste. Furthermore, the strengths corresponding to each age of the cement-based paste co-doped with silica fume and fly ash increased more rapidly than those of the pure cement-based paste, particularly during the early ages. Therefore, considering the priority of rapid hardening and early strength, it is recommended to co-dope fly ash and silica fume into the shotcrete mixture in this environment.